2012
DOI: 10.1051/0004-6361/201219130
|View full text |Cite
|
Sign up to set email alerts
|

Dust shell model of the water fountain source IRAS 16342–3814

Abstract: Aims. We investigate the circumstellar dust shell of the water fountain source IRAS 16342-3814. Methods. We performed two-dimensional radiative transfer modeling of the dust shell, taking into account previously observed spectral energy distributions (SEDs) and our new J-band imaging and H-and K S -band imaging polarimetry obtained using the VLT/NACO instrument. Results. Previous observations expect an optically thick torus in the equatorial plane because of a striking bipolar appearance and a large viewing an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…Both these flux densities are significantly in excess of the values (~ 113 & 30 mJy at 0.886 & 1.3 mm) derived from an extrapolation of the 2-D dust radiative-transfer model fit to IRAS 16342’s SED and near-IR polarised light imaging (Fig. 1 of Murakawa & Izumiura 2012), in which the dominant mass component is a 1 M ⊙ torus of radius 700 − 1000 AU that includes grains with a radius up to 10 μ m.…”
Section: Resultsmentioning
confidence: 76%
“…Both these flux densities are significantly in excess of the values (~ 113 & 30 mJy at 0.886 & 1.3 mm) derived from an extrapolation of the 2-D dust radiative-transfer model fit to IRAS 16342’s SED and near-IR polarised light imaging (Fig. 1 of Murakawa & Izumiura 2012), in which the dominant mass component is a 1 M ⊙ torus of radius 700 − 1000 AU that includes grains with a radius up to 10 μ m.…”
Section: Resultsmentioning
confidence: 76%
“…In bipolar PPNs such as I18276, it is expected that the CDS has an optically thick dust torus/disc in the equatorial region and an envelope, which characterises the lobe shape. In our separate paper on the bipolar PPN IRAS 16342-3814, we needed an additional optically thick, geometrically thin disc inside the torus (Murakawa & Izumiura 2012). For I18276, we tried both model geometries, but found that the inner disc is not necessary.…”
Section: Model Assumptionsmentioning
confidence: 99%
“…The H and KS band data were taken with the Wollaston prism to measure the polarisation. The data were reduced following the same method as before (Murakawa & Izumiura 2012). Standard star data were used to calibrate the surface brightness and the polarisation, and also served to estimate the size of the point spread function (PSF).…”
Section: Observational Constraintsmentioning
confidence: 99%
“…However, here we have a stronger correlation between the PPNe and the black body curve. This is presumably due to the fact that the far-infrared colours are more sensitive to the temperature of the cold dust component, which contributes most of the flux from the SEDs of PPNe (e.g., IRAS 16342−3814,Murakawa & Izumiura 2012). There are some objects, which deviate from the black body curve, that occupy the…”
mentioning
confidence: 99%